HUBUNGAN INDEKS MASSA TUBUH DENGAN KECEPATAN BERJALAN PADA LANSIA DI PPRSLU BUDI SEJAHTERA BANJARBARU - Firdaus, Muhammad Rizqi; Cahyawati, Wiwit Agung Sri Nur; Yasmina, Alfi; Noor, Zairin; Wahyuni, Wahyuni (Homeostasis, 2024)
Abstract: The walking speed is one of the indicators of the fitness in the elderly. One of the factors that influence walking speed is the Body Mass Index (BMI). This study aimed to determine the relationship between BMI and walking speed in the elderly. This cross-sectional study involved 40 elderly individuals living in PPRSLU Budi Sejahtera Banjarbaru who met the inclusion criteria. Data on walking speed were collected using the 4 Meters Walk Test. The relationship between BMI and walking speed was analyzed using Pearson correlation. The mean BMI was 23.4±4.6 kg/m2, the average walking speed was 0.44±0.18 m/s, and no elderlies with normal walking speed were found. There was a negative, moderate, and significant relationship between BMI and walking speed in elderly individuals with normal BMI (r = -0.528; p = 0.014), but no significant relationships were found in underweight and overweight-obese BMI categories (underweight: r = 0.387; p = 0.520; overweight-obese: r = -0.342; p = 0.231). In conclusion, there is a significant relationship between normal BMI and walking speed in the elderly living in PPRSLU Budi Sejahtera. Keywords: walking speed, body mass index, 4 Meters Walk Test, elderly Abstrak: Kecepatan berjalan merupakan salah satu tolok ukur kebugaran lansia. Salah satu faktor yang mempengaruhi kecepatan berjalan adalah indeks massa tubuh (IMT). Penelitian ini bertujuan mengetahui hubungan IMT dengan kecepatan berjalan lansia. Penelitian cross sectional ini melibatkan 40 lansia di PPRSLU Budi Sejahtera Banjarbaru sesuai kriteria inklusi. Pengambilan data kecepatan berjalan menggunakan 4 Meters Walk Test. Hubungan IMT dan kecepatan berjalan dianalisis dengan uji Pearson correlation. Didapatkan rerata IMT sebesar 23,4±4,6 kg/m2, sedangkan kecepatan berjalan adalah 0,44±0,18 m/s dan tidak ada yang mempunyai kecepatan berjalan normal. Terdapat hubungan negatif, moderat, dan bermakna antara IMT dengan kecepatan berjalan lansia dengan IMT normal (r = -0,528; p = 0,014), tetapi tidak terdapat pada IMT underweight dan overweight-obese (underweight: r = 0,387; p = 0,520; overweight-obese: r = -0,342; p = 0,231). Dapat disimpulkan bahwa terdapat hubungan bermakna antara IMT normal dengan kecepatan berjalan pada lansia di PPRSLU Budi Sejahtera. Kata-kata kunci: kecepatan berjalan, indeks massa tubuh, 4 meters walk test, lansia